2017
DOI: 10.1016/j.asoc.2017.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Fairness in examination timetabling: Student preferences and extended formulations

Abstract: Variations of the examination timetabling problem have been investigated by the research community for more than two decades. The common characteristic between all problems is the fact that the definitions and data sets used all originate from actual educational institutions, particularly universities, including specific examination criteria and the students involved. Although much has been achieved and published on the state-of-the-art problem modelling and optimisation, a lack of attention has been focussed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 59 publications
0
10
0
1
Order By: Relevance
“…Quality in education has been discussed in one of the following themes: measure the impact of knowledge [3], [20]- [22], teaching quality [23], [24], assessment quality [25] and timetabling quality [26]. Higher Educational Institutions must guarantee quality for all stakeholders: students, teachers, directors, government and society.…”
Section: ) Academic Researchmentioning
confidence: 99%
“…Quality in education has been discussed in one of the following themes: measure the impact of knowledge [3], [20]- [22], teaching quality [23], [24], assessment quality [25] and timetabling quality [26]. Higher Educational Institutions must guarantee quality for all stakeholders: students, teachers, directors, government and society.…”
Section: ) Academic Researchmentioning
confidence: 99%
“…Beberapa survei state-of-the-art dari formulasi exam timetabling problem, disingkat sebagai ETP, dimulai dari algoritma tradisional graph colouring, hingga meta-heuristic dan hyper-heuristic telah dilakukan pada beberapa penelitian [7]. Pendekatan meta-heuristic, disingkat sebagai MH, telah sukses diaplikasikan untuk memecahkan berbagai masalah optimasi dengan kombinasi yang kompleks termasuk dalam pengembangan state-of-the-art pada area penjadwalan.…”
Section: Algoritma Dengan Pendekatan Hyper Heuristicunclassified
“…It was found that the choice function appeared to be the best alternative for SA with reheating move acceptance within the hyper-heuristics approach. Next, Sabar et al [39] introduced a measurement of difficulty index to measure examination difficulty within a hybridization of hierarchical lowlevel graph colouring heuristics approach, whereas Muklason et al [40] investigated the fairness in examination timetabling by introducing multiobjective solution, also using the hyperheuristics approach.…”
Section: Examination Timetabling Problemmentioning
confidence: 99%